Enhancing medical services through machine learning and UAV technology: applications and benefits - Saeed, Rashid A; Saeed, Mamoon M; Ahmed, Zeinab E; Hassan Abdalla Hashim, Aisha (IGI Global, 2024)
This chapter focuses on the enhancement of medical services through the integration of unmanned aerial vehicle (UAV) technology and machine learning algorithms. It explores the broad spectrum of applications and benefits that arise from combining these two technologies. By employing UAVs for automated delivery, medical supplies can be efficiently transported to remote or inaccessible regions, thereby improving access to vital items. Remote patient monitoring, facilitated through UAVs and machine learning, enables real-time data collection and analysis, enabling the early identification of health issues. UAVs equipped with medical equipment and machine learning capabilities enhance emergency medical response by providing immediate assistance during critical situations. Disease surveillance and outbreak management can benefit from the use of UAVs and machine-learning algorithms to identify disease hotspots and predict the spread of illnesses.